Cyberpornography Use And Psychosexual Health Among Emerging Adults In Malaysia - Tan, Soon Aun (2023)
The advancement of Internet-enabled technologies has created a convenient avenue for young people to explore sexuality online, specifically through cyberpornography. The literature has shown mixed findings on the link between cyberpornography use and its effects on psychosexual health. Thus, the present study examined associations between motivations, cyberpornography use, and psychosexual health (sexual self-esteem and psychological distress). The study also explored the mediating role of perceived realism and utility and the moderating role of trait self-control (self-discipline and impulse control) in the direct association between cyberpornography use and psychosexual health. This cross-sectional quantitative study involved 663 self-identified cyberpornography users (Mage = 23.57; SDAge = 2.75). An online survey using Qualtrics was used to collect the study's data. The study variables were measured using the sexual esteem subscale of the Multidimensional Sexual Self-Concept Questionnaire, Kessler Psychological Distress Scale, Brief Self-Control Scale, Pornography Consumption Inventory, and Perceived Realism of Sexually Explicit Internet Materials Scale. This data was analysed using IBM-SPSS Version 26, Partial Least Squares – Structural Equation Modelling (PLS-SEM). In sum, cyberpornography use among the emerging adult participants was moderate. The study's results also indicated that sexual pleasure, sexual curiosity, excitement seeking, and emotional avoidance were the motivations for cyberpornography use. Gender differences were found in motivations and cyberpornography use.